Identification of determinate sesame lines (Sesamum indicum L.): A step forward in vegetable oil: Identification of determinate sesame lines (Sesamum indicum L.): A step forward in vegetable oil - SIMA SINHA (Journal of Oilseeds Research, 2023)
An experiment was conducted at Bihar Agricultural University, Sabour, Bihar in the year 2020 and 2021 during summer season with 11 elite lines Sesame (Sesamum indicum L.) including two national checks (GT-10, TKG-22 and one zonal check JTS-08) to identify genotypes that had determinate habit so that the capsules matured uniformly. Three lines, BRT-04, BRT-08 and BRT-10, were identified as determinate plant type ones and BRT- 09 was identified as semi determinate type.